Through the eyes of the Indian woman: cartography, spatiality and gender in mapping expeditions in Southern Brazil (18th Century) - Denise A S de Moura (Nuevo mundo - Mundos Nuevos, 2022)
Unveiling the spatiality of indigenous women as shown from written and visual narratives of mapping processes is one of the greatest challenges to be taken on by the history of Latin American critical cartography. Despite advances in the fields of indigenous history, women and gender relations, themes such as native women and territoriality, an aesthetic of absence, neglect and disappearance is still strongly evident. Through written documents, a map and ethnographic data from Jê peoples, this article offers a skeletal methodological path taken to reach the spatial subjectivity of indigenous women in a mapping expedition to the hinterlands of Southern Brazil that took place between the years 1768-1773.